1982
DOI: 10.1159/000225596
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Immunodepression and Metabolic Immunotherapy

Abstract: The effects of administration of phenformin and clofibrate to 32 breast cancer patients who underwent radical mastectomy and suffered from hormonal metabolic disturbances involving a decline in immunologic response were investigated. It was demonstrated that treatment with these drugs during 2–7 months results in an improvement in metabolic parameters and delayed hypersensitivity reaction to DNCB, tuberculin and candidin (75.5% of cases), an increase in T lymphocyte count (56.3%) and an improvement of the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Currently, phenformin is not used in clinical practice due to it side effects (mainly lactic acidosis) observed in patients with non-compensated diabetes. It is worthy of note that during more than a 10-year-long experience of phenformin administration to patients without advanced diabetes, Dilman and Berstein [122-127] observed no cases of lactic acidosis or any other side effects. We believe that results analysis of long-term administration of this drug as well as other antidiabetic biguanides (buformin and metformin) to non-diabetic animals is important for understanding the links between insulin and longevity and between insulin and cancer.…”
Section: Pharmacological Effects On Gh/insulin/igf-1 Signaling Patmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, phenformin is not used in clinical practice due to it side effects (mainly lactic acidosis) observed in patients with non-compensated diabetes. It is worthy of note that during more than a 10-year-long experience of phenformin administration to patients without advanced diabetes, Dilman and Berstein [122-127] observed no cases of lactic acidosis or any other side effects. We believe that results analysis of long-term administration of this drug as well as other antidiabetic biguanides (buformin and metformin) to non-diabetic animals is important for understanding the links between insulin and longevity and between insulin and cancer.…”
Section: Pharmacological Effects On Gh/insulin/igf-1 Signaling Patmentioning
confidence: 99%
“…Biguanides were used as a component of the so-called metabolic rehabilitation of breast and colon cancer patients [109,122,123]. The total of 324 patients (182 with breast cancer and 142 with colon cancer) treated by surgery of the primary tumor were randomly divided into control and treatment groups.…”
Section: Antidiabetic Drugs and Cancer Risk In Diabetic Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…72 In addition to forgetting the pioneer studies by Prof. V.M. Dilman more than 40 y ago, demonstrating a significant association with increased total and diseasefree survival upon the inclusion of the metformin's older cousin phenformin as a long-term adjuvant modality of metabolic rehabilitation of post-operative colorectal and breast cancer patients, [73][74][75] some authors start to prematurely conclude that metformin and metformin-like drugs can be just "cancer drugs for diabetics" with anticancer activities exclusively confined to hyperinsulinemic subjects with insulin-sensitive carcinomas. 6 Although we can anticipate that it will take another 2 to 3 y to enroll all the patients in the numerous metformin-based cancer clinical trials that are currently underway, and it may be 3 to 4 y before the trials results are published in peer-reviewed journals, the recently reported study by Bonnani et al 5 concluded that the anticancer activity of metformin will be restricted to breast cancer patients with high body mass index (BMI) and insulin resistance.…”
Section: Cancer Metabolic Diseases and Metforminmentioning
confidence: 99%
“…However there were no cases of lactic acidosis or any other side effects of phenformin given to patients without advanced diabetes. 26,[32][33][34] We believe that the analysis of results of long-term administration of this drug as well as another antidiabetic biguanides (buformin and metformin) to nondiabetic animals is very important for better understanding links between insulin and longevity. In this paper we critically rewieved available data on effects of antidiabetic biguanides on lifespan of worms, flies, mice, and rats.…”
mentioning
confidence: 99%